Technical Efficiency in the Informal Manufacturing Enterprises: Firm level evidence from an Indian state - Seethamma Natarajan, Rajesh Raj S.N
The small and medium enterprise sector plays a pivotal role in the socio-economic development and growth of nations. But there is evidence that the firms in this sector are less efficient than those in the large enterprise sector. Hence it is imperative to examine their efficiency levels in order to identify the factors that contribute inefficiency in these firms and to generate information for designing support policies for them. In this study, level and sources of technical efficiency in the unorganised manufacturing sector in the Indian state of Kerala is examined using translog stochastic frontier production function. The analysis is conducted for five broad industry groups and the sector as a whole using firm level data. The findings show that high levels of technical inefficiency, which reduce their potential levels significantly, characterize the unorganised manufacturing enterprises in Kerala. Regarding the factors contributing to inefficiencies, it is observed that size, ownership, region (location) and nature of seasonality of operation significantly influence technical efficiency level in most of the industry groups. We also find that credit availability and employment of hired labour play an important role in explaining technical efficiency levels.